2018
DOI: 10.3390/biom8040126
|View full text |Cite
|
Sign up to set email alerts
|

Heme Dissociation from Myoglobin in the Presence of the Zwitterionic Detergent N,N-Dimethyl-N-Dodecylglycine Betaine: Effects of Ionic Liquids

Abstract: We have investigated myoglobin protein denaturation using the zwitterionic detergent Empigen BB (EBB, N,N-Dimethyl-N-dodecylglycine betaine). A combination of absorbance, fluorescence, and circular dichroism spectroscopic measurements elucidated the protein denaturation and heme dissociation from myoglobin. The results indicated that Empigen BB was not able to fully denature the myoglobin structure, but apparently can induce the dissociation of the heme group from the protein. This provides a way to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…Experiments using the zwitterionic detergent N,N -dimethyl- N -dodecylglycine betaine showed that the inclusion of a series of RTILs had no impact on the partial denaturation and heme-loss from myoglobin. This result was intriguing since some of the same RTILs were shown previously to enhance myoglobin denaturation by guanidinium HCl (GuHCl) and urea [10,12,21]. These differences in behavior highlight the still unresolved questions of the chemical mechanism by which different RTILs stabilize or destabilize protein structure and activity.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Experiments using the zwitterionic detergent N,N -dimethyl- N -dodecylglycine betaine showed that the inclusion of a series of RTILs had no impact on the partial denaturation and heme-loss from myoglobin. This result was intriguing since some of the same RTILs were shown previously to enhance myoglobin denaturation by guanidinium HCl (GuHCl) and urea [10,12,21]. These differences in behavior highlight the still unresolved questions of the chemical mechanism by which different RTILs stabilize or destabilize protein structure and activity.…”
Section: Introductionmentioning
confidence: 93%
“…There are unanswered questions at both the basic, fundamental levels up through the increased complexity of in vivo and ecological investigations. A number of literature reports in recent years have focused on characterizing the specific interactions of RTILs with various classes of biomolecules or individual molecules including proteins, nucleic acids, polysaccharides, and lipids [7,10,11,12,13]. These studies often target the mechanism of interaction between a subset of RTILs with a specific target [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ILs have many potential applications in biochemistry and biomedical technology such as drug delivery, enzymatic reaction enhancement, and use as biomaterials. The biomass solubilization [1,2,3,4] and protein structural stabilization and destabilization mechanisms [5,6,7,8,9] of ILs in aqueous solution have been characterized extensively. These studies have primarily focused on either the molecular diversity of IL pairs and the differential effects ion pairs have on activity or the mechanisms by which different IL species disrupt protein structure/function.…”
Section: Introductionmentioning
confidence: 99%